2021
DOI: 10.3390/diagnostics12010075
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers in Interstitial Cystitis/Bladder Pain Syndrome and Its Impact on Therapeutic Outcome

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is defined as a chronic bladder disorder with suprapubic pain (pelvic pain) and pressure and/or discomfort related to bladder filling accompanied by lower urinary tract symptoms, such as urinary frequency and urgency without urinary tract infection (UTI) lasting for at least 6 weeks. IC/BPS presents significant bladder pain and frequency urgency symptoms with unknown etiology, and it is without a widely accepted standard in diagnosis. Patients’ pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 223 publications
(295 reference statements)
0
15
0
Order By: Relevance
“…Urinary proteins had long been considered to have a diagnostic role in bladder dysfunction or bladder outlet dysfunctions [ 4 , 5 , 7 , 8 ]. However, owing to variations in urine collection, different renal conditions, and medical comorbidities, urine levels of biomarkers varied widely in the studies of OAB, IC/BPS, and DV-related BOO [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary proteins had long been considered to have a diagnostic role in bladder dysfunction or bladder outlet dysfunctions [ 4 , 5 , 7 , 8 ]. However, owing to variations in urine collection, different renal conditions, and medical comorbidities, urine levels of biomarkers varied widely in the studies of OAB, IC/BPS, and DV-related BOO [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urine contains proteins and is excreted from the kidney or bladder wall. Previous studies have found that some urinary cytokines, chemokines, and oxidative stress biomarkers are elevated in patients with overactive bladder (OAB), DO, IC/BPS, and DV [ 4 , 5 , 6 , 7 , 8 ]. Although urine-based biomarkers may provide valuable diagnostic and prognostic tools for the clinical assessment of LUTDs and treatment guidelines, the urine proteins currently found in women with different bladder disorders varied widely and are poorly reproducible [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The marker 8-OHdG is a common and sensitive biomarker of oxidative DNA damage [ 35 ]. Interestingly, in case of 100 µM NE treatment, the concentration of 8-OHdG was significantly decreased, however some previous papers highlighted that hormonal stress is able to induce oxidative DNA damage (reflected by an elevated 8-OHdG level) in human oral keratinocyte cells, and also in hepatocytes of rats [ 36 , 37 ]; further, an increased 8-OHdG level was detected in the urine of patients with interstitial cystitis [ 38 , 39 ]. Based on these previous data, the above-mentioned paradoxical effect may be explained rather by the over-compensating processes of uroepithelial cells, than the protective role of NE against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers have made a great effort to investigate the pathogenesis of UTI, most studies have been carried out using various animal models, and the evidence from human bladders remains limited 13 . Recent research has suggested using intravesical PRP injection might have a therapeutic effect in treating lower urinary tract disorders due to regenerative deficiency 14 .…”
Section: Discussionmentioning
confidence: 99%